Demographic and Clinical profile of Neonates admitted in a NICU of a Tertiary Care Hospital in Bangladesh - Chowdhury, Kanta; Hossain, M Monir; Hoque, Md Mahbubul; Jahan, Rowshan Akhter; Zaman, Shekufe; Salauddin, Gazi; Sarker, Lamia (Northern International Medical College Journal, 2025)
Background: Neonatal morbidity and mortality remain major public health challenges in Bangladesh, particularly among critically ill neonates requiring intensive care. Identifying the clinical profile and outcomes of neonates admitted to tertiary care facilities is essential for improving neonatal survival and guiding preventive strategies. Methods: This cross-sectional study was conducted in the Department of Neonatal Medicine, Bangladesh Shishu Hospital and Institute, Dhaka, from 1st January 2023 to 30th June 2023. A total of 382 neonates were admitted to the Neonatal Intensive Care Unit (NICU) during this period were included. Data on demographic characteristics, morbidity patterns and outcomes were collected and analyzed using SPSS version 25. Results: Among 382 neonates admitted to the Neonatal Intensive Care Unit (NICU), males predominated (63.6%). Most were term infants (81.7%) and delivered by normal vaginal delivery (57.6%). Birth asphyxia (41.9%) was the leading cause of morbidity, followed by preterm low birth weight (18.3%) and neonatal sepsis (13.1%). The overall mortality rate was 41.4%, with birth asphyxia (54.4%) being the primary cause of death. Most admissions occurred within 24–72 hours of life (55.2%). Conclusion: Birth asphyxia, neonatal sepsis and prematurity were identified as the major causes of neonatal morbidity and mortality in this tertiary care setting. Northern International Medical College Journal Vol. 16 No. 1-2 July 2024-January 2025, Page 740-744